Cerâmicas porosas a base de zircônia na forma de filmes suportados preparados a partir de emulsões - Santos, Douglas da Silva Fabricio dos [UNESP] (2015)
Porous films of sulfated zirconia were produced by emulsion templates associated to the sol-gel process that allows the synthesis at low temperature, compositional accuracy, microstructural control and chemical homogeneity capabilities. The films were prepared from aqueous suspensions of basic sulfate zirconium with different molar ratios Zr4+: SO42-. The emulsion from this different suspensions was used to obtain the porous films had 60% in mass of non-polar phase (decahydronaphtalen - DHN) and 3% of nonilphenol etoxylate surfactant (IGEPAL®850). The films were deposited by dip-coating method and dryed at 60ºC. Previously was evaluated the films formation prepared from a emulsion of molar ratio Zr4+: SO42- of 15: 1 on different substrates such as carbon steel, copper, aluminum, PET (polyethylene terephthalate) and glass. Carbon and copper substrates suffered oxidation due to the acid character of the colloidal suspension, while aluminum, PET and glass had good adherence visually and homogeneity in the films formation. The films deposited in glass substrates from the aqueous suspensions and the respectivy emulsions showed bands in infrared region corresponding to the presence of free and mono- bidentate sulfates in the zirconia, which have decomposition temperature around 500ºC according the thermogravimetry. The use of emulsion favors the formation of the porous structure in the ceramic film and increasing the sulfate amount occurs the increase of pores volume (until 2,4 cm3g-1) and porosity (until 83,7%) and in the solid real density (from 2,17 to the reference until 2,75 g cm-3 in high sulfate quantity). The macroporous size was around 60 m for all the samples and there is evidence of mesoporous with 5 nm. Structures like needles were formed in the films surface, which are more homogeneous in the films prepared by emulsions. Thus, zirconia ceramic films were obtained with promising features...